2011
DOI: 10.1007/s11250-011-9801-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nkedi Zebu and Ankole cattle to tick infestation and natural tick-borne, helminth and trypanosome infections in Uganda

Abstract: A cross-sectional study was conducted in Soroti district of Uganda to establish important traits of Nkedi Zebu and Ankole cattle regarding their production performance responses to natural infections of trypanosomes, gastrointestinal nematodes, Theileria parva, Babesia bigemina, Anaplasma marginale and tick infestations. Over four visits between October 2006 to August 2007, tick counts were performed and blood, faecal samples and sera were collected from the Nkedi Zebu (295) and Ankole (165) cattle from 86 her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Overall, our findings are similar to what has been observed in recent tick surveys in Uganda (Byaruhanga et al 2015 ; Magona et al 2011 ; Muhanguzi et al 2020 ; Rubaire-Akiiki et al 2006 ), as well as in nearby Rwanda (Bazarusanga et al 2007 ), Tanzania (Lynen et al 2007 ), DRC (Kalume et al 2013 ), and Zimbabwe (Sungirai et al 2015 ). Interestingly, Byaruhanga et al ( 2015 ) obtained similar frequencies in Uganda for A. variegatum , R. appendiculatus , A. gemma , and R. pulchellus as in our study, an indication of their possible endemic stability in the country.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our findings are similar to what has been observed in recent tick surveys in Uganda (Byaruhanga et al 2015 ; Magona et al 2011 ; Muhanguzi et al 2020 ; Rubaire-Akiiki et al 2006 ), as well as in nearby Rwanda (Bazarusanga et al 2007 ), Tanzania (Lynen et al 2007 ), DRC (Kalume et al 2013 ), and Zimbabwe (Sungirai et al 2015 ). Interestingly, Byaruhanga et al ( 2015 ) obtained similar frequencies in Uganda for A. variegatum , R. appendiculatus , A. gemma , and R. pulchellus as in our study, an indication of their possible endemic stability in the country.…”
Section: Discussionsupporting
confidence: 90%
“…In Uganda, the overall threat of ticks and tick-borne diseases to public health is not well known, partly due to limited knowledge on the natural diversity of ticks across the country. In fact, the most detailed and nationally representative surveys of tick species in Uganda that involved a variety of animal species were done in the 1970s, or earlier (Matthysee and Colbo 1987 ; Tukei et al 1970 ), while the most recent studies have focused mainly on either specific geographical areas or veterinary aspects (Byaruhanga et al 2015 ; Magona et al 2011 ; Rubaire-Akiiki et al 2006 ; Socolovschi et al 2007 ). According to Walker et al ( 2014 ), there are approximately 27 species of ticks infesting domestic animals in Uganda that are of socio-economic, veterinary, and human health importance.…”
Section: Introductionmentioning
confidence: 99%
“…This study also established a higher non-clinical T. parva infection prevalence among the lower age group (though marginal significant) and the oldest group as previously reported [ 13 , 14 ]. This is a reflection of a lower ability to control T. parva infection during primary disease challenges which tends to improve in older cattle.…”
Section: Discussionsupporting
confidence: 88%
“…The field visits coincided with the long and short rainfall seasons when pastoral cattle keepers did not have to trek long distances in search of pastures. It is also during these periods that tick burdens are high with possibilities of comparatively high T. parva infection challenge [ 13 , 14 , 36 ]. The overall prevalence of non-clinical T. parva (30%) infection established in this study is within the expected limits given the fact that indigenous cattle are frequent carriers of piroplasms associated with non-clinical low parasitaemia.…”
Section: Discussionmentioning
confidence: 99%
“…To control these parasites, other control methods can be explored such as the selection of tick-resistant cattle. Studies done on Nkedi Zebu and Ankole exposed to tick infestation have shown intraracial differences in tick load [ 7 ], and a difference in infestation was noted according to the cattle ages. The works done by Mattioli et al [ 8 ] on N'Dama, Gobra Zebu, and their crossbred products showed an interracial difference of tick infestations, suggesting that the selection of the cattle can be also based on ticks resistance.…”
Section: Introductionmentioning
confidence: 99%